Influence of Organic Liquid Fertilizer on The Growth and Production of Purple Eggplant (Solanum melongena) - Agnes Refiana Br Sembiring; Tharmizi Hakim; Desi Sri Pasca Sari Sembiring (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
Eggplant production in Indonesia is still low and only accounts for 1% of the world's needs, this is because the cultivation culture is still not intensive. Infertile soil is also a factor in low eggplant production. In order for growth to be good, it must look at the ideal growing conditions and nutrients in the soil. This study aims to determine the optimal concentration of liquid organic fertilizer in increasing the growth and production of purple eggplant plants. The research design applied is a non-factorial Randomized Group Design (RGD) consisting of 1 factor, namely Liquid Organic Fertilizer, with 4 experimental levels, namely P0 (0 ml /l water), P1 (50 ml /l water), P2 (100 ml /l water), P3 (150 ml /l water). The results showed that the concentration of liquid organic fertilizer had a very significant effect on all variables observed, except the number of fruits, fruit weight and production weight were not significantly different. LOF treatment with a concentration of 150 ml/l water gave the best results on the parameters of plant height, stem diameter, number of flowers, number of fruits, fruit length, fruit weight, production weight and production ha/ton